Políticas públicas educacionais e ensino de ciências : dificuldades e potencialidades - Polino, Sandra Garcia (2012)
Public Policy Education has passed through several instances before being implemented in teaching institutions. Particularly in the case of public schools, normally, action with greater proportion have been developed through programs and projects that derive from maintaining institutions, such as the Federal Government, through MEC (Ministry of Education and Culture) and the Departments of Education in states and cities. This research aims to investigate how managers, represented by coordinators and directors of the State Department of Education, as well as teachers of public schools of the state, have perceived and enabled public policies focused on teaching scientific areas. Data were collected through interviews with focal groups, and a qualitative methodological approach, with an analysis guided by a Discursive Textual Analysis, was utilized. From the research results, it was possible to identify two essential categories for understating the analysis. The first category, Appropriation and Reinterpretation of Public Policy Education and Science Teaching has approached the perception of the educators who made part of the study on public policies and that were present in their pedagogical practices, besides the way they participated in the re-elaboration of these education policies in order to implement them in school. The second category, Difficulties in Dealing with Public Policy Education and the Possibilities Glimpsed to Minimize them , has processed the barriers found in the teaching action that result in consequences for Science teaching, and the alternatives proposed by research subjects utilized to minimize such difficulties. Moreover, the subcategories have addressed the discontinuity and non-contextualization of public policy education, the lack of partnership between universities and schools, difficulties in obtaining resources and accessing projects in the Science field, and the impact of lack of appreciation for the teaching profession. Thus, from this research, it was possible to verify that the course for implementing education programs and projects has constituted one of the gears of public policy education, for which all people involved are important and in charge of the process results.